Aneurysmal right ventricular outflow in an adult patient with unrepaired Tetralogy of Fallot and an absent pulmonary valve. Issue 2 (9th November 2021) - Mishra, Anand K.; Rana, Pratyaksha; Raja, Javid; Bansal, Vidur; Singhal, Manphool
Abstract: Background: Absent pulmonary valve (PV) is a rare and severe variant seen in only 3% to 6% of patients with tetralogy of Fallot (TOF). Fetuses with this combined condition who survive through birth typically need intervention in infancy or early childhood because of respiratory distress, heart failure, or failure to thrive. Discussion: Here, we describe the case of a 37 year old gentleman who presented with a diagnosis of TOF with absent PV, hugely dilated right and left pulmonary arteries and an aneurysmal right ventricular outflow. Conclusion: TOF with absent PV surviving into adulthood is a rarity. An aneurysmal right ventricular outflow tract in an unrepaired case of TOF has not been described before. Massively dilated left and right pulmonary arteries as in this case can cause significant and even life‐threatening airway compromise, thus necessitating early surgical repair.